Binary Co–Ni oxide nanoparticle-loaded hierarchical graphitic porous carbon for high-performance supercapacitors. (15th January 2020) - Liu, Yin; Xiang, Cuili; Chu, Hailiang; Qiu, Shujun; McLeod, Jennifer; She, Zhe; Xu, Fen; Sun, Lixian; Zou, Yongjin
Abstract: Heteroatom doped graphitic porous carbon is highly desirable for electrochemical applications because of its excellent conductivity and high surface area. In this study, highly uniform Co-Ni oxide nanoparticle-loaded B, N-doped hierarchical graphitic porous carbon was prepared through a dual pyrolysis process. Graphene dispersed chitosan hydrogel was first used as a precursor to fabricate the porous carbon (GCS–C) at 700 °C. Co and Ni oxide nanoparticles were further anchored on the porous carbon through chemical reduction and calcined at high temperature. The structure of the porous carbon was optimized by the introduction of graphene to the chitosan hydrogel. The graphitic degree of the porous carbon was significantly improved by the Co and Ni species. The heteroatom B and N were found to be well doped in the composite. These features enable the composite to be an excellent candidate for supercapacitor electrodes. The composite demonstrates a high capacitance (1266.7 F g −1 at 1 A g −1 ) and excellent stability.